Graphene quantum dot modified glassy carbon electrode for the determination of doxorubicin hydrochloride in human plasma - Nastaran Hashemzadeh; Mohammad Hasanzadeh; Nasrin Shadjou; Jamal Eivazi-Ziaei; Maryam Khoubnasabjafari; Abolghasem Jouyban (Elsevier, 2016)
Low toxic graphene quantum dot (GQD) was synthesized by pyrolyzing citric acid in alkaline solution and characterized by ultraviolet--visible (UV-vis) spectroscopy, X-ray diffraction (XRD), atomic force microscopy (AFM), spectrofluorimetery and dynamic light scattering (DLS) techniques. GQD was used for electrode modification and electro-oxidation of doxorubicin (DOX) at low potential. A substantial decrease in the overvoltage (−0.56 V) of the DOX oxidation reaction (compared to ordinary electrodes) was observed using GQD as coating of glassy carbon electrode (GCE). Differential pulse voltammetry was used to evaluate the analytical performance of DOX in the presence of phosphate buffer solution (pH 4.0) and good limit of detection was obtained by the proposed sensor. Such ability of GQD to promote the DOX electron-transfer reaction suggests great promise for its application as an electrochemical sensor.